THE ACTUAL QUESTIONS OF LEGAL PROTECTION OF ATMOSPHERIC AIR FROM THE POLLUTING SUBSTANCES IN DRIVEN GAS VEHICLES - Ситніченко, Олена Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the actual queistions of legal protection of atmospheric air from the polluting substances in driven gas vehicles were considered. The main disadvantages of the national laws, which need to be improved and adapted to EU legislation, were foud out. The possible ways of it’s elimination were determined. Methods: a set of general and special methods of scientific knowledge – the terminology, logical-semantic, functional, system-structural, logical and normative. Results: the analysis of the current situation of the bringing of national environmental protection practices in a field of atmospheric air protection in accordance with the standards of the European Union was conducted. It’s shows the complexity of the problem and the absence of the developed mechanisms for controlling the environmental state of the air. Such mechanisms would ensure it’s predicted quality and the observance of environmental standards. These facts create the barriers for the harmonization of environmental legislation, and establishe non-compliance with the requirements of the European Environmental Protection Law. It’s necessary to improve legislation by implementing the EU Directives and to reform the relevant monitoring system. Discussion: a number of inconsistencies in approaches and standards for the protection of atmospheric air by the EU and Ukraine, and the shortcomings of the national legislative and normative acts, that need to be improved and adapted to EU legislation, and the ways of it’s elimination. Thus, the analysis of the current situation of the bringing of national environmental protection practices in a field of atmospheric air protection in accordance with the standards of the European Union was conducted. It’s shows the complexity of the problem and the absence of the developed mechanisms for controlling the environmental state of the air. Such mechanisms would ensure it’s predicted quality and the observance of environmental standards. These facts create the barriers for the harmonization of environmental legislation, and establishe non-compliance with the requirements of the European Environmental Protection Law. It’s necessary to improve legislation by implementing the EU Directives and to reform the relevant monitoring system.